Presence of Multiple Drug Resistant Enterococcus faecalis with Virulence Traits in Household Dahi - S Bhagya; Archana Chandran; R.L Rathish; M.P Rahila; E.C Athulya (The Indian Veterinary Journal, 2023)
Dahi is a traditional fermented milk made using undefined starter cultures. An integrated approach based on phenotypic and genotypic methods were conducted to investigate the virulence traits and multiple drug resistance of Enterococcus faecalis strains isolated from dahi. Eight strains of E.faecalis were isolated from house hold dahi. Multiple drug resistance towards Ceftriaxone and Vancomycin was exhibited by the strain E.faecalis ADMH 19. The gene coding for gel E and asa1 were detected and no gene coding for clyA was observed. The presence of Enterococci with multiple drug resistance and virulence factors in homemade foods can be a potential risk to the consumers.